Let's solve your equation step-by-step.
2
x
+
3
=
5
2
x
Solve Exponent.
2
x
+
3
=
5
2
x
log
(
2
x
+
3
)
=
log
(
5
2
x
)
(Take log of both sides)
(
x
+
3
)
*
(
log
(
2
)
)
=
2
x
*
(
log
(
5
)
)
x
+
3
=
(
log
(
5
)
log
(
2
)
)
*
(
2
x
)
x
+
3
=
2.321928
*
2
x
x
+
3
=
4.643856
x
(Simplify both sides of the equation)
x
+
3
−
4.643856
x
=
4.643856
x
−
4.643856
x
(Subtract 4.643856x from both sides)
−
3.643856
x
+
3
=
0
−
3.643856
x
+
3
−
3
=
0
−
3
(Subtract 3 from both sides)
−
3.643856
x
=
−
3
−
3.643856
x
−
3.643856
=
−
3
−
3.643856
(Divide both sides by -3.643856)
x
=
0.823304